2019
DOI: 10.1038/s41385-019-0159-z
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-galactosylceramide enhances mucosal immunity to oral whole-cell cholera vaccines

Abstract: Cholera is a severe diarrheal disease caused by the bacterium Vibrio cholerae (V. cholerae) that results in 3-4 million cases globally with 100,000-150,000 deaths reported annually. Mostly confined to developing nations, current strategies to control the spread of cholera include the provision of safe drinking water and improved sanitation and hygiene, ideally in conjunction with oral vaccination. However, difficulties associated with the costs and logistics of these strategies have hampered their widespread i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 38 publications
2
20
0
1
Order By: Relevance
“…It was also shown that a novel whole-cell killed Vibrio cholerae strain and recombinant cholera toxin subunit B (CTB) could be successfully loaded as antigens in SmPill ® minispheres. Consistent with the previous findings, Davitt and colleagues demonstrated that combining these antigens and α-GalCer in SmPill ® minispheres enhanced intestinal lipopolysaccharide and CTB-specific IgA responses and induced intestinal antigen-specific Th1 responses ( Figure 2) [88].…”
Section: Oral (Gastrointestinal) Vaccinessupporting
confidence: 88%
See 1 more Smart Citation
“…It was also shown that a novel whole-cell killed Vibrio cholerae strain and recombinant cholera toxin subunit B (CTB) could be successfully loaded as antigens in SmPill ® minispheres. Consistent with the previous findings, Davitt and colleagues demonstrated that combining these antigens and α-GalCer in SmPill ® minispheres enhanced intestinal lipopolysaccharide and CTB-specific IgA responses and induced intestinal antigen-specific Th1 responses ( Figure 2) [88].…”
Section: Oral (Gastrointestinal) Vaccinessupporting
confidence: 88%
“…Some iNKT cell agonists have been investigated as adjuvants to enhance immune responses in immunotherapy and vaccination strategies [86]. Lavelle and colleagues demonstrated the potential of the iNKT cell activator α-Galactosylceramide (α-GalCer) as an oral adjuvant to enhance intestinal immune responses induced by experimental whole-cell killed ETEC [87], Vibrio cholerae [88] and Helicobacter pylori [89] antigens in mouse models. In addition, a novel oral delivery-integrated system named Single Multiple Pill ® (SmPill ® ), containing oil-in-water emulsions formulated as 1 mm minispheres, was reported to effectively protect and enhance the release of various drugs in targeted intestinal regions [90].…”
Section: Oral (Gastrointestinal) Vaccinesmentioning
confidence: 99%
“…The killing of mice and subsequent analysis of cellular responses were performed as previously described. 23 Splenocytes and MLN cells were plated at 1 × 10 6 cells/ml in complete Roswell Park Memorial Institute (cRPMI). Cells were stimulated for 72 h at 37 °C/5%CO 2 with the following stimuli: boiled Hel 305 lysate antigens (1 µg/ml) or purified MP305 (1 µg/ml).…”
Section: Methodsmentioning
confidence: 99%
“…Fecal pellet supernatants and serum samples were collected and prepared as previously described. 22,23 Mice were placed into individual cages and five fresh fecal pellets were collected in 500 µl of cold fecal pellet buffer (0.1 mg/ml Soybean trypsin inhibitor (Sigma Aldrich), 1% Bovine Serum Albumin (BSA), 25 mM ethylenediaminetetraacetic acid (EDTA) (Gibco), 1 mM PEFABloc (Sigma Aldrich), 50% Glycerol in 1× PBS)) and kept on ice for 4 h. Samples were then weighed, emulsified, centrifuged at 15,400 × g for 5 min at 4 °C and supernatants were stored at −20 °C until further use. Blood was obtained from mice by incision into the tail vein.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation